Evaluation strategies for measuring pneumococcal conjugate vaccine impact in low-resource settings. (3rd August 2022) - von Mollendorf, Claire; Lim, Ruth; Choummanivong, Molina; Sychareun, Vanphanom; Vilivong, Keoudomphone; Lai, Jana Y. R.; Chan, Jocelyn; Dunne, Eileen M.; Phommachanh, Sysavanh; Moore, Kerryn A.; Ortika, Belinda D.; Gray, Amy; et al.
ABSTRACT: Objectives: Pneumococcal conjugate vaccines (PCVs) are effective in reducing pneumococcal disease. We measured 13-valent PCV (PCV13) effect on different pneumococcal outcomes using diverse studies in Lao People's Democratic Republic. Methods: Studies included: pre-PCV13 population-based record review of hospitalized childhood pneumonia cases; acute respiratory infection (ARI) study post-PCV13 to demonstrate effectiveness (VE) against hypoxic pneumonia; invasive pneumococcal disease (IPD) surveillance in all ages (2004–2018); carriage studies in children hospitalized with ARI (2013–2019); community carriage surveys pre- and post-PCV13. Results: Annual pneumonia incidence rate in children pre-PCV13 was 1, 530 (95% confidence interval [CI] 1, 477–1, 584) per 100, 000. Adjusted VE against hypoxic pneumonia was 37% (95% CI 6–57%). For IPD, 85% (11/13) of cases were due to vaccine-types pre-PCV13, and 43% (3/7) post-PCV13 in children aged <5 years; for ≥5 years, 61% (27/44) and 42% (17/40), respectively. For ARI cases, adjusted VE for vaccine-type carriage was 39% (95% CI 4–60) in <5 year olds; slightly higher than community surveys (23% [95% CI 4–39%] in 12–23 month olds). Conclusions: Despite limited baseline data, we found evidence of PCV13 impact on disease and carriage. Our approach could be used in similar settings to augment existing WHO PCV evaluation guidelines.